Ion-specific effects of divalent ions on the structure of polyelectrolyte brushes - Xu, Xin (2020)
Polyelectrolyte brushes consist of charged polymer chains attached on one end to a surface at high densities. They are relevant for many practical applications ranging from biosensors to drug delivery to colloidal stability. Their structure and functionality can be dramatically influenced by multivalent counterions in the solution environment. In this work, the surface forces apparatus (SFA) and atomic force microscopy (AFM) were used to investigate the effects of three alkaline earth divalent cations, Mg2+, Ca2+, and Ba2+, on the structures of polystyrenesulfonate (PSS) brushes tethered to mica and silicon oxide surfaces. While all these ions caused significant shrinkage of the height of the PSS brushes, strong ion-specific effects were observed. Mg2+ and Ca2+ caused homogeneous shrinkage; Ba2+ led to pinned-micelle like inhomogeneous structures. Isothermal titration calorimetry (ITC) demonstrated that this ion specificity was mainly caused by the difference in binding energy between sulfonate groups and the divalent cations. Considering the abundance of divalent cations in industrial processes, natural environments, and biological systems, the understanding of strong ion-specific effects of divalent counterions is of great importance for theoretical studies and various applications involving polyelectrolytes.